Pengalaman Komunikasi Pria Pegiat Gym Pengguna Media Sosial Instagram - Kuswandanu, Taqiyuddin; A, Weni; Ema (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research aims to determine the motives, meanings and communication experiences of male gym activists regarding posts related to gum. This research uses a qualitative research method with a phenomenological approach. Data was obtained through an in-depth interview process as well as field and online observations. The theory used is Alfred Schutz's phenomenological theory and Participatory Media Culture theory. The outcomes of the research indicate that the "cause" motive stems from feelings of insecurity or lack of confidence regarding one's physique, while the "goal" motive is characterized by a desire to garner attention, praise, and feedback from one's followers, as well as to capture a moment in time. Regarding gym-related posts, the participants viewed them as a means of conveying messages, expressing themselves, eliciting feedback, and serving as a source of motivation. Additionally, the participants' experiences of positive feedback and likes from their followers contributed to their posts serving as a motivational tool for their followers, while negative experiences took the form of vulgar comments and impolite direct messages from unknown individuals. This study employs phenomenological and communication experience approaches and focuses on men who work out at the gym.